Mapping of the perigastric lymphatic network using indocyanine green fluorescence imaging and tissue marking dye in clinically advanced gastric cancer. Issue 2 (February 2022) - Park, Ji-Hyeon; Berlth, Felix; Wang, Chaojie; Wang, Sen; Choi, Jong-Ho; Park, Shin-Hoo; Suh, Yun-Suhk; Kong, Seong-Ho; Park, Do Joong; Lee, Hyuk-Joon; Kwak, Yoonjin; Kim, Woo Ho; et al.
Abstract: Background: Using indocyanine green (ICG) fluorescence imaging and tissue marking dyes (TMDs), perigastric lymphatic mapping and their pathological correlation were examined to see whether ICG staining covers all metastatic lymph nodes (LNs) in advanced gastric cancer (AGC). Methods: Patients with AGC who underwent open distal or total gastrectomy were enrolled. ICG was serially injected intraoperatively into the subserosa along the greater and lesser curvatures. Stomach specimens were examined under a near-infrared camera. ICG-stained LNs were named, excised, and tattooed with different colored TMDs to retrace the exact location after pathological examinations. Results: A total of 687 LNs and 69 LN stations were examined from 11 patients. The map of the perigastric lymphatic network showing the topography of ICG-stained and ICG-unstained LNs, including metastatic information, was successfully reconstructed. The average number of ICG-stained and ICG-unstained LNs were 23.6 ± 12.3 (37.8%) and 38.8 ± 17.1 (62.2%), respectively. LN metastases were present in 28 LN stations of 8 patients. Of 8 cases with LN metastases, 40% (11.1–75% per case) of metastatic LNs were stained by ICG. Of 28 metastatic LN stations, 21 (75.0%) were covered by ICG, and actual metastatic LNs were stained in 16 LN stations (57.1%). In 4/8 cases (50%), all metastatic LN stations showed ICG signals. Conclusions: ICG fluorescence imaging and TMD are useful tools for visualizing the perigastric lymphatic network and retracing the exact location of ICG-stained LNs in AGC. However, ICG imaging is still not recommended for selective LN dissection in AGC because of the limited staining of perigastric LNs.